ESRA19-0564 Challenges of epidural anaesthesia and sedation for prolonged microvascular lower limb surgery in a complex patient with severe psoriasis: learning from failures and successes. (30th August 2019) - Holland, M; Wilson, K; Matthews, J; Ramsden, A; Galitzine, S
Abstract : Background and aims: Our orthopaedic centre has extensive experience of performing prolonged lower limb free tissue transfer (LLFTT) under epidural anaesthesia and sedation (EA&S) with excellent surgical and patient-reported outcomes. We present our first and only flap failure in our series of over 80 patients anaesthetised using this technique and discuss the lessons learned. Methods: A 55-year-old man required excision of osteomyelitis and LLFTT. His comorbidities included severe psoriasis, BMI 42, 'restless legs' syndrome and anxiety. He consented to EA&S. A challenging epidural insertion — due to severe psoriasis on his back — was accomplished with ultrasound assistance; however, extensive preoperative use of emollient led to great difficulty affixing the epidural catheter. Nevertheless, a 12 hr procedure was accomplished under EA&S and the patient was transferred to HDU for overnight care. Results: Later post-operatively, the patient became severely restless and uncooperative, got out of bed and put weight on the operated leg, with resulting flap compromise and epidural displacement. Despite two rescue surgeries the flap failed. Psychiatrist's advice was required to manage his anxiety before the second flap was successfully undertaken some weeks later. Conclusions: This case highlights the importance of patients' prehabilitation for successful LLFTT. The extent of this patient's psychiatric problems had not been fully appreciated preoperatively. Management of mental comorbidities must be considered as important as that of somatic conditions. As importantly, where dermatological disease or its treatment may interfere with the success of EA, alternative methods of catheter fixation should be considered and topical therapy modified in the perioperative period.